Gender Interpretations Of EmotionalExpressive Means In Women’s And Men’s Speech In The Uzbek Language (Eurasian Journal of Humanities and Social Sciences, 2025)
This article analyzes the gender-specific features of emotional-expressive language means used in male and female speech in the Uzbek language from a linguopragmatic point of view. The study highlights the influence of the gender factor on the communicative situation, the use of more emotional units in female speech, as well as such features as elegance, colorfulness and greater use of emotional units, as well as brevity, firmness and less emotionality in male speech, based on examples. The frequency of use and semanticpragmatic load of female and male speech units, expressions, evaluative words and expressive forms are studied within the framework of gender linguistics.